1985
DOI: 10.1111/j.1095-8339.1985.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of fungi in the nutrition of stream invertebrates

Abstract: Dead leaves falling into streams are an important food source for many invertebrates. They are generally made more palatable and more nutritious if they are first colonized by aquatic hyphomycetes and other micro‐organisms. At least two mechanisms appear to be responsible for this conditioning effect: microbial production (addition of easily digested microbial compounds to the nutritionally poor leaf substrate), and microbial catalysis (conversion of indigestible leaf substances into digestible subunits by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(164 citation statements)
references
References 54 publications
7
155
2
Order By: Relevance
“…This is in line with previous studies (Rong et al, 1995 andZubrod et al, 2015b) that observed no significant correlations between leaf ergosterol contents and consumption by shredding invertebrates. Conversely, Bärlocher (1985) reported strong relationships between leaf nutritional quality (characterized by nitrogen-rich fungal biomass accumulation) and invertebrate feeding, in accordance with the concept of compensatory feeding (i.e., an increase in leaf consumption by shredders to fulfill their energetic requirements despite the lower quality food on offer). Here, invertebrate Gammarus feeding rates followed complex patterns according to litter decomposition stage ( Fig.…”
Section: Drought and Tbz Stress Effects Along The Aquatic Detrital Fosupporting
confidence: 67%
“…This is in line with previous studies (Rong et al, 1995 andZubrod et al, 2015b) that observed no significant correlations between leaf ergosterol contents and consumption by shredding invertebrates. Conversely, Bärlocher (1985) reported strong relationships between leaf nutritional quality (characterized by nitrogen-rich fungal biomass accumulation) and invertebrate feeding, in accordance with the concept of compensatory feeding (i.e., an increase in leaf consumption by shredders to fulfill their energetic requirements despite the lower quality food on offer). Here, invertebrate Gammarus feeding rates followed complex patterns according to litter decomposition stage ( Fig.…”
Section: Drought and Tbz Stress Effects Along The Aquatic Detrital Fosupporting
confidence: 67%
“…As seen in earlier studies, the present study also reveals increase in leaf nitrogen (corroborates studies by Bärlocher 1985, Webster & Benfield 1986 and decrease in leaf phosphorus and leaf phenolics. The nitrogen elevation was highest in Kaiga stream and Kadra dam during post-monsoon season coinciding with high species richness, conidial output and diversity especially in banyan leaf (see Table 3, 5).…”
Section: Discussionsupporting
confidence: 93%
“…This allochthonous material is colonised by aquatic fungi and bacteria and subsequently by stream macroinvertebrates, particularly those from the functional feeding group described as shredders (Bärlocher, 1985;Cummins et al, 1989;Webster and Benfield, 1986). The rate at which these stream biota process the leaves is influenced by many factors such as stream chemistry and water temperature (Kaushik and Hynes, 1971).…”
Section: Introductionmentioning
confidence: 99%